Elastography of multicellular aggregates submitted to osmo-mechanical stress. (July 2015) - Leroux, Charles-Edouard; Palmier, Joelle; Boccara, Albert Claude; Cappello, Giovanni; Monnier, Sylvain
Abstract Tumors are subjected to mechanical stress generated by their own growth in a confined environment, and by their surrounding tissues. Recent works have focused on the study of the growth of spherical aggregates of cells, spheroids, under controlled confinement or stress. In this study we demonstrate the measurement of spatially and temporally resolved deformation maps inside spheroids while applying an osmo-mechanical stress. We use full field optical coherence tomography, a high resolution imaging technique well suited for real-time measurements of deformation in living tissues under stress. Using the spherical symmetry of the experiment, we compare our data to a mechanical modeling of the spheroid as a continuous medium. We estimate the viscoelastic parameters of spheroids and discuss the apparent tissue anisotropy after the osmo-mechanical stress.